Unveiling the Plasmodium inositol (pyro)phosphate pathway: Highlighting inositol polyphosphate multikinase as a novel therapeutic target for malaria - Abigail Obuobi; Neils B. Quashie; Nancy Odurowah Duah-Quashie; Jon R. Sayers (PLoS ONE, 2025)
Plasmodium falciparum malaria is fatal if left untreated. Treatment is hampered by drug-resistant variants of the malaria parasite, highlighting the need to explore unique pathways for the development of new drugs with different mechanisms of action. Kinases in the inositol phosphate signaling pathway (IPP), and its products play many important roles in energy metabolism and signal transduction, making them attractive drug targets. In this exploratory study we investigated the potential of P. falciparum IPP as a novel and attractive pathway for antimalarial drug discovery, employing a combined in silico and molecular approach. The sequences and structures of the putative P. falciparum inositol phosphate kinases were characterized in silico . Experimental validation across laboratory strains and a clinical isolate confirmed the p.Pro375Gln substitution in IPMK1, providing the first evidence of this variant in field isolates. We provide molecular evidence of the existence of IPP genes in P. falciparum and suggest that targeting this pathway could be detrimental to the parasite. We identify P. falciparum inositol polyphosphate multikinase (IPMK) as a promising drug target due to its unique sequence and structural characteristics. These results serve as a guide for future experimental validation.